Trojan horse treatment based on PEG-coated extracellular vesicles to deliver doxorubicin to melanoma in vitro and in vivo. Issue 1 (31st December 2022) - Patras, Laura; Ionescu, Aura Elena; Munteanu, Cristian; Hajdu, Renata; Kosa, Andreea; Porfire, Alina; Licarete, Emilia; Rauca, Valentin Florian; Sesarman, Alina; Luput, Lavinia; Bulzu, Paul; Chiroi, Paul; et al.
ABSTRACT: Tailoring extracellular vesicles (EVs) as targeted drug delivery systems to enhance the therapeutic efficacy showed superior advantage over liposomal therapies. Herein, we developed a novel nanotool for targeting B16.F10 murine melanoma, based on EVs stabilized with Polyethylene glycol (PEG) and loaded with doxorubicin (DOX). Small EVs were efficiently enriched from melanoma cells cultured under metabolic stress by ultrafiltration coupled with size exclusion chromatography (UF-SEC) and characterized by size, morphology, and proteome. To reduce their clearance in vivo, EVs were PEGylated and passively loaded with DOX (PEG-EV-DOX). Our data suggested that the low PEG coverage of EVs might still favor EV surface protein interactions with target proteins from intratumor cells, ensuring their use as "Trojan horses" to deliver DOX to the tumor tissue. Moreover, our results showed a superior antitumor activity of PEG-EV-DOX in B16.F10 murine melanoma models in vivo compared to that exerted by clinically applied liposomal DOX in the same tumor model. The PEG-EV-DOX administration in vivo reduced NF-κB activation and increased BAX expression, suggesting better prognosis of EV-based therapy than liposomal DOX treatment. Collectively, our results highlight the promising potential of EVs as optimal tools for systemic delivery of DOX to solid tumors.